Heterogeneous radiological response to chemotherapy is associated with poor prognosis in advanced non‐small‐cell lung cancer. Issue 24 (24th October 2021) - Ryu, Woo Kyung; Kim, Jung Soo; Park, Mi Hwa; Lee, Minkyung; Kim, Hyun‐Jung; Ryu, Jeong‐Seon; Lim, Jun Hyeok
Abstract: Background: A heterogeneous radiological response is frequently observed in cancer patients and could reflect tumor heterogeneity. We investigated the prognostic impact of heterogeneous radiological responses in patients with advanced non‐small‐cell lung cancer (NSCLC) who received platinum‐based chemotherapy. Methods: The treatment response according to Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria was evaluated in 212 patients with advanced NSCLC who received platinum‐based chemotherapy. Patients with partial response (PR) or stable disease (SD) were classified into "PR homo, " "PR hetero, " "SD homo, " and "SD hetero" by the presence of a heterogeneous radiological response, and survival was compared between groups. We also compared survival based on the presence of metabolic responses in lesions with heterogeneous radiological responses. Results: Fifty‐two patients (24.5%) were classified as PR, 112 patients (52.8%) as SD, and 48 patients (22.7%) as progressive disease (PD). There was no significant difference in progression‐free survival (PFS) and overall survival (OS) between the PR homo and PR hetero groups. The SD homo group had a longer PFS and OS than the SD hetero group. In the SD hetero group, patients with increased maximum standardized uptake value (SUVmax) in lesions with heterogeneous radiological responses had a shorter PFS than those with a stable SUVmax. Conclusions: The presence of lesions with radiological heterogeneity was associated with disease progression and poor prognosis in the SD group. Patients with heterogeneous radiological responses require careful monitoring. Abstract : Patients with heterogeneous radiological responses in the SD group had a shorter PFS and OS. In particular, patients with increased SUVmax in lesions with heterogeneous radiological responses had a shorter PFS than patients with a stable SUVmax. The presence of lesions with radiological heterogeneity was associated with disease progression and poor prognosis in the SD group.